The Security and efficient management of distributed behavior in the context of Internet of Things (IoT) - Medileh, Saci (Universty of Eloued جامعة الشهيد حمة الأخضر, 2022)
الملخص: الاستخدام الشائع للأجهزة الذكية والشبكات، أدى لتوسع وانتشار بيئة أنترنت الأشياء، وأصبح من الممكن التوصيل المباشرة للأشياء المادية بالإنترنت باستخدام المتحكمات الدقيقة. تعتبر الجوانب الأمنية والموزعة عوامل مهمة لحماية وإدارة الكائنات المتصلة من الأشخاص أو البرامج الضارة. علاوة على ذلك، يمكن تثبيت الكائنات المتصلة في بيئة غير موثوقة، حيث تكون هذه الكائنات ديناميكية للغاية، وعرضة للأعطال، وعادة ما يتم نشرها في ظروف بعيدة وقاسية، مما يقود إلى تنفيذ إدارة السلوكيات الموزعة للحفاظ على أداء الشبكة ولتوفير نظام مستقل فعال. لذلك، تطرح بيئة إنترنت الأشياء أسئلة مهمة وتقدم تحديات جديدة للأمن، في الواقع، يمثل الأمن مصدر قلق كبير عندما يتم نشر الشبكات على نطاق واسع. لذلك، فإن البحث عن حلول أمنية مناسبة أمر ضروري لضمان جمع وتخزين المعلومات من طرف الأجهزة الذكية ومشاركتها مع الاحتياطات الأمنية اللازمة لضمان السرية والموثوقية. يهدف هذا العمل إلى اقتراح تقنيات وتقييم المخططات الموحدة والآمنة لبروتوكولات تبادل المفاتيح في بنى شبكات إنترنت الأشياء الحديثة التي تتكون من كائنات (عقد استشعار)، وعقد سحابية، وهواتف ذكية، ومستخدمين نهائيين. علاوة على ذلك، لتنفيذ أو دمج الحلول الأمنية غير المتماثلة لتشفير البيانات القائمة على تبادل مفاتيح الإنترنت، وسيتم تقييمها في محاكاة أو سيناريو على أجهزة الشبكات الحقيقية. Abstract : فرنسية أو انجلزية When the use of smart devices and networks becomes common, the Internet of Things (IoT) field allows the direct connection of physical objects to the Internet using microcontrollers. The security and distributed aspects are considered important factors to protect and manage connected objects from malicious people and/or software. Furthermore, the connected objects can be installed in a hostile environment, where they are highly dynamic, prone to faults, and typically deployed in remote and harsh conditions, which leads to implementing the management of distributed behaviors to maintain the performance of the network and to provide an efficient autonomous system. Therefore, IoT generates important questions and introduces new challenges for security. In fact, security is a major concern when networks are deployed on a large scale. Therefore, looking for adequate security solutions is necessary to ensure that smart devices capture and share information with appropriate security measures. This work aims to propose and evaluate the standardized, secure schemes for key exchange protocols in modern Internet of Things architectures consisting of objects (sensor nodes), cloud nodes, smartphones, and end-users. Moreover, to implement/integrate of asymmetric security solutions based on Internet Key Exchange (IKE), they will be evaluated in simulation or a scenario on real networking devices.
أطروحة دكتوراه تخصص: .إعلام آلي في العلوم الدقيقة
Keywords: الأمان؛ التشفير؛ الأنظمة الموزعة؛ إدارة السلوكيات الموزعة؛ انترنت الأشياء؛ الأجهزة المتصلة؛ الأجهزة الذكية; Security; Cryptography; Distributed System; Management of distributed behaviors; Internet of Things; Connected Devices; Smart Devices.